The Facts about Mothballs - Brett Bultemeier (EDIS)
Mothballs are widely available for purchase and familiar to many people. However, mothballs are one of the most misused products, and their misuse can cause harmful effects to people or the environment. This new 4-page publication of the UF/IFAS Pesticide Information Office will give the basics about what mothballs are, where they can be used, and their status as a pesticide. Written by Brett W. Bultemeier. https://edis.ifas.ufl.edu/pi289